Guideline-directed medical therapy prescribing patterns and in-hospital outcomes among heart failure patients during COVID-19 - Pratyaksh K. Srivastava; Alexandra M. Klomhaus; Asim Rafique; Pooja S. Desai; Lori B. Daniels; Clyde W. Yancy; Eric H. Yang; Gregg C. Fonarow; Rushi V. Parikh (American Heart Journal Plus, 2024)
Study objective: The association of prior to admission guideline-directed medical therapy (GDMT) use in patients hospitalized with Heart Failure with Reduced Ejection Fraction (HFrEF, ejection fraction ≤40 %) and Coronavirus Disease 2019 (COVID-19) with in-hospital outcomes has not been well studied. Design/setting/participants/interventions/outcome measures: Using the American Heart Association's Get With The Guidelines Heart Failure Registry, we identified HFrEF patients presenting with acute decompensated heart failure (ADHF) and compared rates of GDMT prescription between those presenting prior to and during the pandemic. In a subgroup of patients with a concomitant COVID-19 diagnosis, we evaluated the association of prior to admission GDMT use with in-hospital mortality and severe COVID-19. Results: 23,899 patients were admitted with HFrEF during the pandemic (2/16/20–3/24/21) and 26,459 patients were admitted in the year prior (2/16/19–2/15/20). In this overall cohort, prior to admission ACEI/ARB/ARNI (45.6 % vs 48.1 %, p < 0.0001) and BB (56.9 % vs 62.4 %, p < 0.0001) use was lower among admitted HFrEF patients during the pandemic when compared to the year prior. Rates of ACEI/ARB/ARNI, MRA, and triple therapy (ACE/ARB/ARNI + BB + MRA) prescription at discharge were higher during the pandemic compared to the year prior. Among a subgroup of those with HFrEF and COVID-19 (n = 333), prior to admission GDMT use was not associated with in-hospital mortality or severe COVID-19. Conclusion: We found no association between prior to admission GDMT use and in-hospital mortality or severe COVID-19 among HFrEF patients admitted with ADHF and COVID-19. GDMT prescription at discharge for HFrEF patients overall has remained either similar or improved during the pandemic.